Rancangan Pembelajaran Inovatif Abad 21 Pada Materi Desain Interior dan Eskterior dengan Model Pembelajaran Smk Pada Jurusan Dpib SMK Negeri 1 Adiwerna - Maaufur Rojihi (Cakrawala: Jurnal Pendidikan, 2022)
Innovative learning in the 21st century is activity-oriented to practice essential skills within the framework for 21st century skills, namely life and career skills, innovation and learning skills, and information, media, and ICT skills. Learning characteristics to train these essential skills lead to an interactive, holistic, integrative, scientific, contextual, thematic, effective, collaborative, and student-centered learning process, so that in its implementation educators can design activities by choosing learning methods / models that can accommodate the overall characteristics comprehensively. Production-based learning and learning models in the world of work, educational quality support and training oriented to the school's relationship with the industrial world and the business world in implementing production units in schools. Teaching Factory is a concept of learning in a real atmosphere, so as to bridge the competency gap between industry needs and school knowledge. Synergy between schools and industry is a key element of success in TEFA, as it will be a connecting means for cooperation between schools and industry. Industrial Work Practices is an educational, training and learning activity carried out in the Business World or the Industrial World in an effort to approach or to improve the quality of vocational high school (SMK) students